Relationship between 18-F-fluoro-deoxy-d-glucose uptake and expression of glucose transporter 1 and pyruvate kinase M2 in intrahepatic cholangiocarcinoma. Issue 7 (July 2015) - Suzuki, Hideki; Komuta, Mina; Bolog, Altan; Yokobori, Takehiko; Wada, Satoshi; Araki, Kenichiro; Kubo, Norio; Watanabe, Akira; Tsukagoshi, Mariko; Kuwano, Hiroyuki
Abstract Background Cholangiocellular carcinoma is characterized by elevated glucose consumption, resulting in an increased uptake of 18F-2-fluoro-2-deoxy-d-glucose (18F-FDG). This study investigates the relationship between 18F-FDG uptake and tumour glucose metabolism. Methods This was a retrospective analysis of 19 patients with cholangiocellular carcinoma. Immunohistochemistry for glucose transporter 1 and pyruvate kinase type M2 were performed. Overall tumour glucose metabolism was evaluated by measuring 18F-FDG uptake and the protein expression levels of glucose transporter 1 and pyruvate kinase type M2. Results 18F-FDG uptake had a strong positive correlation with histological differentiation. Both tumour status (p = 0.044) and tumour size (p = 0.011) were correlated with primary tumour 18F-FDG uptake. Glucose transporter 1 expression correlated with histological differentiation (p = 0.017), while pyruvate kinase type M2 expression tended to correlate with lymph node metastasis (p = 0.051). Glucose transporter 1 expression was strongly related to the standard uptake value (p = 0.001), but that of pyruvate kinase type M2 was not (p = 0.461). Conclusions Glucose transporter 1 expression exhibits a strong correlation with 18F-FDG uptake in cholangiocellular carcinoma tissue, while pyruvate kinase type M2 expression was not associated with fluoro-2-deoxy-d-glucose uptake. In addition to its glycolytic function, pyruvate kinase type M2 has a variety of roles and its expression may enhance tumour cell invasion and promote the lymph node metastasis of intrahepatic cholangiocarcinoma.